Infectious Diseases Selected Entries from the Encyclopedia of Sustainability Science and Technology - Kanki, Phyllis.; Grimes, Darrell Jay. (Springer New York : Imprint: Springer, 2013)
Infectious Diseases: Selected Entries from the Encyclopedia of Sustainability Science and Technology presents authoritative, peer-reviewed contributions from leading experts on a wide range of major infectious diseases of global importance. Infectious diseases account for more than 17 million deaths each year worldwide. While modern medicine and technology have diminished the threat of many of these pathogens in high-income countries, the ever present threats of re-emerging infections, population mobility, natural disasters, and pathogen genetic variability are but some of the reasons for the dynamic threat of this broad category of risks to human health. An indispensable resource for students and scientists, the volume also covers some of the new technologies currently under development for infectious disease prevention, treatment, and eradication. The greater part of the infectious disease burden remains in the tropics, where low and middle-income countries lack the resources, infrastructure, and health systems to mount or sustain control efforts. Many contributions describe the efforts of the scientific research community and international donor agencies to achieve the integrated goals of vigilant surveillance, improved and cost-effective diagnostics, and treatment for sustainable disease control. Describes the dynamic nature of infectious disease agents and their complex interactions with the environment and theirhuman and animal hosts Covers new technologies for antibiotics, vaccines, and treatment Features several contributions on waterborne infectious diseases, including enteric viruses and bacterial pathogens in the ocean Provides an excellent introduction for those entering the field, as well as new insights for advanced researchers and industry experts